Rural E-Commerce Promoting the Development of Small Holder Farmers in Rivers State, Nigeria - Adira Augustine (PT SOLUSI EDUKASI BERDIKARI, 2025)
Effective rural e-commerce as a factor of development of small holder farmers in the new era has become a fundamental, crucial, and interesting topic for researchers in the past few decades. And in quest to specifically identify its impacts, challenges and platforms responsible for the promotion and development of small holder farmers operating e-commerce in Rivers State Nigeria, a descriptive survey design comprised of 84 rural small holder farmers with a self-made survey questionnaire was adopted. Using Cronbach Alpha Reliability Coefficient tool, and by analyzing the reliability coefficient, Mean, Standard Deviation and Z-test of the hypotheses, the study deduced that small holder farmers in the area utilizes Facebook, Instagram, YouTube and whatsApp as e-commerce platforms that improves farmers income, performance and enhances agricultural development in the area. Finally, the paper put forward suggestive measures hopeful of ensuring sustainable agriculture, promotes and develop e-commerce operation in the study area. Figure 1 Shown below.